2013
DOI: 10.1007/s00246-013-0797-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Prolonged Length of Intensive Care Unit Stay After Stage I Palliation: A Report from the National Pediatric Cardiology Quality Improvement Collaborative

Abstract: The objective of this study is to identify predictors of prolonged intensive care unit (ICU) length of stay (LOS) for single ventricle patients following Stage I palliation. We hypothesize that peri-operative factors contribute to prolonged ICU stay among children with hypoplastic left heart syndrome (HLHS) and its variants. In 2008, as a part of the Joint Council on Congenital Heart Disease initiative, the National Pediatric Cardiology-Quality Improvement Collaborative established a data registry for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Younger age, lower weight, heart failure, higher VIS, pulmonary hypertension, delayed sternal closure, greater severity of illness at post-operative admission, BUN, nitric oxide treatment, tracheobronchomalacia, peritoneal dialysis, low cardiac output, health-care associated infections, and noninfectious pulmonary complications are associated with prolonged intubation in patients undergoing surgery for CHD [20] [21] [22] [23]. Premature extubation with the need for reintubation is associated with longer ICU LOS [24]. In our patients, duration of ventilation greater than 20 days was associated with the longest CCU LOS.…”
Section: L Mahan Et Al World Journal Of Cardiovascular Surgerymentioning
confidence: 99%
“…Younger age, lower weight, heart failure, higher VIS, pulmonary hypertension, delayed sternal closure, greater severity of illness at post-operative admission, BUN, nitric oxide treatment, tracheobronchomalacia, peritoneal dialysis, low cardiac output, health-care associated infections, and noninfectious pulmonary complications are associated with prolonged intubation in patients undergoing surgery for CHD [20] [21] [22] [23]. Premature extubation with the need for reintubation is associated with longer ICU LOS [24]. In our patients, duration of ventilation greater than 20 days was associated with the longest CCU LOS.…”
Section: L Mahan Et Al World Journal Of Cardiovascular Surgerymentioning
confidence: 99%
“…Additionally, it has been shown that CABSI can prolong length of stay (LOS) by up to 24 days . Prior studies have shown that each additional hospital day after surgery costs approximately $500 . While CABSI is definitively prevented by not having central access, this is not always possible, and studies have highlighted the importance of standardized methods for prevention …”
Section: Introductionmentioning
confidence: 99%
“…3 Prior studies have shown that each additional hospital day after surgery costs approximately $500. 4 While CABSI is definitively prevented by not having central access, this is not always possible, and studies have highlighted the importance of standardized methods for prevention. 5 There are limited published data on the incidence of CABSI in children with congenital heart disease undergoing congenital cardiac surgery (CCS).…”
Section: Introductionmentioning
confidence: 99%
“…Few LOS models have been developed for children or infants undergoing cardiac surgery, although the pediatric heart network investigators 18,19 have reported on risk factors for prolonged length of stay following the Glenn and Fontan procedures. Currently, there is no precise definition of prolonged length of stay in the literature, but previous studies using the PHN SVR dataset have used a threshold at the 75th percentile 20,21 . Schwartz et al 18 defined prolonged LOS after Norwood as the median length of stay for transplant-free survivors who later underwent Glenn procedure.…”
mentioning
confidence: 99%